Biodigestory moat associated with floodwaters built for treatment of single-family sewage (Research, Society and Development, 2019)
Brazil has approximately 31 million inhabitants living in rural and isolated communities, data presented by the Brazilian Institute of Geography and Statistics (IBGE). Sadly, of this expressive number, only 22% are covered by the basic sanitation service. In addition to this, approximately 5 million Brazilians are in a situation where they do not even have a bathroom in their homes (IBGE, 2013). The lack of basic sanitation in rural areas compromises the quality of water, water table, water body, affects aquatic life, and contributes to the proliferation of numerous parasitic and infectious diseases. In view of this scenario, an association of two existing systems was developed: the biodigest fossa developed by Embrapa and the flooded built, associating both systems from the need to treat wastewater and ash and provide complete rural sanitation. The purpose of this project is the complete treatment of rural domestic effluent, minimize the impact of pollution of water bodies, protection of the environment and contribute to health, reducing the rates of diseases caused by lack of sanitation.